Dental Health Status and Associated Factors in the Deprived Population Covered by Rural Dental Insurance Program in the Province of Kerman/Iran - Sabermahani, Asma; Jafari Sirizi, Mohammad; Shaker, Zinab; Hassanzadeh, Rasool; Malekmohammadi, Tayebeh; Hasheminejad, Naimeh (Journal of Dentistry Indonesia, 2024)
Tooth decay is a widespread disease with considerable financial and psychological costs. Objective: The aim of this study was to investigate dental health of a large sample of people covered by rural insurance program in Kerman province. Methods: A sample size of 5000 was determined among people living in villages and towns with a population of less than 20000 who are all covered by dental rural insurance program. The DMFT/dmft index was assessed in five target age groups using the WHO oral health measurement standard form. Demographic and socioeconomic status of participants was also recorded. The percentage of people in need of immediate treatment was also recorded. STATA software version 14. Regression analysis and chi square tests were used for further data analysis. Results: Questionnaires of 3248 participants qualified to enter the study. The least mean DMFT score was related to the 12 year target group (3.1 ± 2.7) and the 65-74 year target group revealed the highest mean DMFT score (20.8 ± 12.2). In most target groups, the decayed component of DMFT/dmft index contributed the most to the overall score. DMFT index revealed an increase compared to the results of 2012 survey. Overall, 8.3 percent of individuals were in need of immediate treatment. Tooth brushing status and the use of fluoridated toothpaste was related to lower DMFT/dmft scores. Conclusion: Despite the rural dental insurance coverage, the DMFT/ dmft has not decreased in this more deprived population of Kerman province. An evaluation of this program is needed to detect possible defaults. Dental health education with a special emphasis on toothbrushing with a fluoride containing toothpaste can help improve dental health.